Localización, distribución y diseño de una planta recicladora de vidrio (residuo sólido) - Jaramillo Valdiviezo, Franklin Roberto (2012)
This project consists of 8 chapters which have been distributed as follows: The first chapter (background) is about the entire introduction to the collection of solid waste (glass) in the Metropolitan District of Quito (DMQ), a history of it, and general and specific project objectives. The second chapter (requirements for the design of the plant) is about the impact of solid waste collection (glass) in the Metropolitan District of Quito (DMQ) in environmental management, the requirements for the implementation of a glass recycling plant the Metropolitan District of Quito (DMQ), the existing problems with the collection of glass, the limits of the project, environmental management decisions, the study of the location of the plant by the use of land, logistics and transport of matter premium from collection sites to the plant. The third chapter (design process) indicates how they will split the processes within the plant since the arrival of raw materials to final product output after passing through the recycling process, give you a map of indicators with which a one look will I know the operating strategy of the plant in its various processes. The fourth chapter (components of the plant) is the capacity of the plant after completing the study location and design of it, I will also design the finished product has been chosen to result in the glass processing. The fifth chapter (suitable plant) examines the machinery that exists in the plant that must be obtained from abroad and locally will be in addition to an assessment of the machine and select the type of plant that wanted to have the physical space as and the distribution chosen for it. The sixth chapter (calculations in the ground) this chapter will examine the design of physical spaces within the plant, delimit the areas of operations, offices, production, parking and so on, give the dimensions of each area of the plant according to factors design. The seventh chapter (economic and financial) will analyze the net present value (NPV), Internal Rate of Return (IRR) of these indicators will the feasibility or otherwise of the implementation of the plant The eighth chapter (conclusions and recommendations), these findings help to verify objectives, and the import of the implementation of a glass recycling plant.